Neuroanatomy of the ankylosaurid dinosaurs Tarchia teresae and Talarurus plicatospineus from the Upper Cretaceous of Mongolia, with comments on endocranial variability among ankylosaurs - Paulina Carabajal, Ariana (2018)
Ankylosaur braincase and endocranial morphologies are poorly known. Furthermore, cranial endocasts have been described for fewer than ten taxa so far. The complete inner ear morphology is known for only three species – Euoplocephalus tutus, Kunbarrasaurus ieversi, and Pawpawsaurus campbelli. Here, the first cranial endocast morphologies are presented for the Mongolian Cretaceous ankylosaurids Talarurus plicatospineus and Tarchia teresae. The study of paleoneurological features of these Mongolian taxa adds novel anatomical information to both species allowing the first comparison with ankylosaurids from North America. The development of a cerebellar flocculus that leaves an impression on the vestibular eminence – floccular recess – is observed in Euoplocephalus, Talarurus and T. teresae. Because this structure hasn't been identified in any nodosaurid so far, its presence in ankylosaurid cranial endocasts may represent a possible synapomorphy with unknown paleobiological implications.